International Financial Reporting Standards IFRS and Their Impact on Cooperatives in Colombia by December 31, 2011 - Rendón Alvarez, Bibiana; Montaño Orozco, Edilberto; Gaitán León, Gabriel (Cuadernos de Administración, 2013)
This paper evaluates the effect of applying the International Accounting Standard (IAS 32) on financial instruments, on social contributions in cooperative entities in Colombia to December 31, 2011, through identification of balance sheet financial statement items: liabilities, equity, capital, and irreducible minimum capital. The aforementioned analysis sought to answer the following questions: what is the effect of applying IAS 32 in the financial structure of cooperatives, in recognizing the social contributions of applying the financial instruments standard, what actions must be performed to minimize the effect of applying the financial instruments standard to social contributions? The work required a sample of 187 cooperative financial sector entities and 173 real sector entities, which reported information to the Colombian Confederation of Cooperatives (Confeccop), corresponding to mandatory reporting by those entities to the Superintendent of the Solidarity Economy (Supersolidaria). It was possible to determine the impact endured by the financial structure of cooperative organizations in their capital component and liabilities, by applying IFRS on financial instruments.